An introduction to organic lasers - Boudrioua, Azzedine; Chakaroun, Mahmoud; Fischer, Alexis (Advanced lasers set., 2017)
One of the biggest challenges of organic optoelectronics is the realization of the first organic laser diode (electrically pumped) which has a very strong potential for many applications. Similar to what happened in the field of inorganic optoelectronics when transforming LEDs into LDs, the race is on to transform an OLED into an OLD. This involves the development of innovative solutions to overcome the difficulties inherent in organic materials and the electric pump. This book presents the elements of physics, materials and technologies that allow us to understand the basics of organic lasers and to capture the progress made. It also provides guidance for future developments towards the organic laser diode.